Heme-nitrosylated hemoglobin and oxidative stress in women consuming combined contraceptives. Clinical application of the EPR spectroscopy - Lobysheva, Irina I.; van Eeckhoudt, Sandrine; Dei Zotti, Flavia; Rifahi, Ahmad; Pothen, Lucie; Beauloye, Christophe; Balligand, Jean-Luc (Free radical biology & medicine, 2017)
An increased risk of venous thromboembolism was identified in young women consuming combined contraceptive pills (CP) suggesting a disturbance of vascular homeostasis but the impact of CP on endothelial function and redox status of the vasculature was not thoroughly analyzed. We measured the bioavailability of nitric oxide (NO), a main mediator of vascular homeostasis in a cohort of young female subjects (n=114) and compared the results in users or not of CPs containing ethinyl estradiol and synthetic progestogens. Vascular NO availability was measured by quantification of the heme-nitrosylated hemoglobin (5-coordinate-α-HbNO) concentrations in venous erythrocytes using Electron Paramagnetic Resonance spectroscopy (EPR). Vascular oxidative status was assessed by measurement of peroxides in plasma, and of the thiol redox state in erythrocytes. In addition, endothelial function was assessed by digital reactive hyperemia pulse tonometry using EndoPAT. We observed that the HbNO level was significantly lower in erythrocytes of subjects consuming CPs versus controls (162±8 and 217±12 nmol/L). This correlated with significantly increased levels of plasma peroxides (1.8±0.1mmol/L versus 0.8±0.1mmol/L in controls) and decreased concentrations of erythrocyte reduced thiols (by 12%). Interestingly, the level of oxidized ceruloplasmin-Cu(II) was also significantly higher in the group consuming CPs. The EndoPAT index showed a trend towards impairment in CP users, and was significantly lower in subjects that consumed CPs containing drospirenone, and had lowest erythrocyte HbNO levels. This cross-sectional cohort study demonstrates that a decrease of HbNO measured by quantitative EPR in human venous erythrocytes is correlated with the development of endothelial dysfunction under CPs consumption, in parallel with increased vascular oxidative stress. [Display omitted] •Hemoglobin nitrosylation measured by EPR reflected vascular NO bioavailability.•Consumption of contraceptive pills decreased hemoglobin nitrosylation (HbNO).•Blood oxidant state increased under consumption of contraceptive pills (CP).•Erythrocyte HbNO concentrations inversely correlated with plasma peroxide levels.•Degree of HbNO decrease and oxidant increase depended on the progestin CP content.